Investigation on Rare Earth Elements Mineralization in Indonesia - , L.D. Setijadji ([Yogyakarta] : Departmentof GeologicalEngineering,Facultyof Engin, 2009)
In Indonesia, Rare Earth Elements (REE) are most possibly present associated with Mesozoic granitic rocks that are distributed in the western Indonesian such as the Tin islands (Bangka, Belitung, Bintan and Singkep) and west-central Kalimantan. Especially granites of the Tin islands are hypothetically potential for REE deposits based on the similarity of their geology with those of REE-producing China and SE Asia granite belts. As initial step two types of REE mineralization styles are investigated in Bangka and Belitung, i.e. placer deposit associated with placer tin and ion-adsorption type within weathering crust. Heavy minerals fractions from tin-bearing placer deposits are prospective for future REE extraction with conditions that we have the technology to handle radioactive elements especially Th and U. On the other hand, lateritic ion-adsorption REE type is also indicated, but further investigations should be done to elucidate its mode of occurrence.